ANALISIS KESALAHAN BERBAHASA DALAM SKRIPSI MAHASISWA SEBAGAI ACUAN PENYUSUNAN BAHAN AJAR MATA KULIAH BAHASA INDONESIA - Lian, Yohanes Pemandi (Jurnal Lazuardi, 2024)
This research aims to describe written Indonesian language errors in aspects of spelling and sentences in the thesis of students at the Widya Mandira Catholic University, Accounting Study Program. This research uses qualitative research by analyzing 25 samples of theses. Based on the research results, it can be concluded that the forms of language errors found in the theses of students of the Widya Mandira Catholic University, Accounting Study Program were in the form of spelling errors including capital letters, italics, writing and punctuation, totaling 311 errors or 58.9%; and sentence errors include errors in sentence structure alignment, parallelism, coherence, and sentence accuracy as much as 217 or 41.1%.